Public Space Users’ Soundscape Evaluations in Relation to Their Activities. An Amsterdam-Based Study - Bild, Edda; Pfeffer, Karin; Coler, Matt; Rubin, Ori; Bertolini, Luca (Frontiers in Psychology, 2018)
Understanding the relationship between people and their soundscapes in an urban context of innumerable and diverse sensory stimulations is a difficult endeavour. What public space users hear and how they evaluate it in relation to their performed or intended activities can influence users’ engagement with their spaces as well as their assessment of suitability of public space for their needs or expectations. While the interaction between the auditory experience and activity is a topic gaining momentum in soundscape research, capturing the complexity of this relationship in context remains a multifaceted challenge. In this paper, we address this challenge by researching the user-soundscape relationships in relation to users’ activities. Building on previous soundscape studies, we explore the role and interaction of three potentially influencing factors in users’ soundscape evaluations: level of social interaction of users’ activities, familiarity and expectations, and we employ affordance theory to research the ways in which users bring their soundscapes into use. To this end, we employ a mixed methods design, combining quantitative, qualitative and spatial analyses to analyse how users of three public spaces in Amsterdam evaluate their soundscapes in relation to their activities. We documented the use of an urban park in Amsterdam through non-intrusive behavioural mapping to collect spatial data on observable categories of activities, and integrated our observations with on site questionnaires on ranked soundscape evaluations and free responses detailing users’ evaluations, collected at the same time from park users. One of our key findings is that solitary and socially interactive respondents evaluate their soundscapes differently in relation to their activities, with the latter offering higher suitability and lower disruption ratings than the former; this points to qualitatively different auditory experiences, analysed further based on users’ open-ended justifications for their evaluations. We provide a methodological contribution (adding to existing soundscape evaluation methodologies), an empirical contribution (providing insight on how users explain their soundscape evaluations in relation to their activities) and a policy and design-related contribution, offering additional insight on a transferable methodology and process that practitioners can employ in their work on the built environment to address the multisensory experience of public spaces.